Drought Stress and Its Impact on Protein in Three Species of Vitex - John A. De Britto; P. Benjamin Jeya Rathna Kumar; D. Herin Sheeba Gracelin; S. Santhana Jency (Journal of Stress Physiology & Biochemistry, 2011)
Drought is one of the most important natural phenomenon which affects on plant growth. When drought stress is imposed different molecular and biochemical responses took place in the plants. The protein profile of three species of Vitex (Vitex trifolia L., Vitex altissima L. and Vitex negundo L.) under normally irrigated condition and severe drought plants was analyzed through SDS-PAGE. Drought stress significantly affects proteins in plants when compared the normal conditioned plants. Several new protein bands were identified in the stressed plants. It seems that Vitex species can be adapted to drought stress conditions. Hence it was concluded that number of new proteins were synthesized in stressed plants for their adaptation in the stressed conditions. These proteins could be used as markers in identifying the stressed plants.